Pengaruh Latihan Kelincahan Terhadap Kemampuan Menggiring Bola Dalam Permainan Futsal Pada Siswa SMA Negeri 3 Tondano - Apolos E. Falagaku; Frans R. Supit; Bacilius Sukadana (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
The problem in this study can be formulated as follows: Is there an effect of agility training on the ability to dribble in futsal games for Tondano 3 Public High School students? The research objective was: the effect of agility training on the ability to dribble in futsal games for Tondano 3 Public High School students. Research Hypothesis: There is an effect of agility training on the ability to dribble in futsal games for Tondano 3 Public High School students. The research method used is an experimental method. The population was all male students of class X SMA Negeri 3 Tondano totaling 20 and the sample was the entire population of 20 people then divided into two groups of 10 people each in the experimental group and 10 people in the control group. Data collection instrument: Ability test dribbling. The research design used: Pre-test and post-test with randomized groups. Testing the hypothesis using statistical techniques with the t test. The results of calculations using the t-test statistic obtained the t observation value of tob = 12.469. Meanwhile, from the table of critical values t with a real level α = 0.05; n1+n2-2 obtained t table value of ttab = 2.101. This fact shows that the value of tob = 12.469 > ttab = 2.101, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.